Architecture, planning & design : Palafox Associates, the first twenty years. (Makati City, Philippines : Palafox Associates, 2010)
Architecture, Planning & Design: Palafox Associates The First Twenty Years is a highly-visual coffee table book featuring more than 150 projects ranging from elite golf-course communities to visionary green buildings. Writers include prominent industry pioneers such as Washington Sycip, Richard Woodling, Ramon Zaragoza and Gina Lopez. Through a documented account of its metamorphoses as an industry stakeholder and corporate citizen of this nation, Palafox Associates hopes to enrich this discussion focused on the renewed imaging of the Filipino architect-planner in a global context. In this volume, Palafox Associates shares its self-reflection in the public realm. Quite unlike previous publications of the same genre, this volume seeks to inspire young architects to appreciate the limitless opportunities within a globalizing milieu for those who persevere in a difficult professional field that is rooted in commitment, excellence, competence, professionalism, ethics and a sensitivity of context.
Foreword -- Message -- Professional and competency paradigms on the global context -- Integrating nature in designing structures and building communities -- Editor's note -- A reminiscing -- Timeline -- Global footprints -- Planning -- Architecture -- Architecture + Planning -- Postcards from the future -- The Palafox Associates team -- Awards and recognitions -- Clients -- International and Philippine consultants -- Directory of staff -- Index -- Featured projects -- Contributors -- Acknowledgements and editorial board -- Copyright page